2006
DOI: 10.1182/blood-2004-12-4856
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 controls vascular platelet recruitment and thrombus adherence in mice by protecting (sub)endothelial VWF from cleavage by ADAMTS13

Abstract: The function of thrombospondin-1 (TSP-1) in hemostasis was investigated in wild-type (WT) and Tsp1 ؊/؊ mice, via dynamic platelet interaction studies with A23187-stimulated mesenteric endothelium and with photochemically injured cecum subendothelium. Injected calcein-labeled WT platelets tethered or firmly adhered to almost all A23187-stimulated blood vessels of WT mice, but Tsp1 ؊/؊ platelets tethered to 45% and adhered to 25.8% of stimulated Tsp1 ؊/؊ vessels only. Stimulation generated temporary endothelium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(149 citation statements)
references
References 47 publications
8
139
0
2
Order By: Relevance
“…In vitro, thrombin, plasmin, and perhaps hemoglobin may inactivate ADAMTS13 [15;16]. Thrombospondin may also protect VWF from cleavage by ADAMTS13 [17]. Based on observations following infusion of normal plasma in patients with genetic deficiency of ADAMTS13, the elimination half-life of ADAMTS13 is approximately 2 days.…”
Section: Adamts13 -Structure and Functionmentioning
confidence: 99%
“…In vitro, thrombin, plasmin, and perhaps hemoglobin may inactivate ADAMTS13 [15;16]. Thrombospondin may also protect VWF from cleavage by ADAMTS13 [17]. Based on observations following infusion of normal plasma in patients with genetic deficiency of ADAMTS13, the elimination half-life of ADAMTS13 is approximately 2 days.…”
Section: Adamts13 -Structure and Functionmentioning
confidence: 99%
“…Average velocity and flux per image were calculated by Matlab software (MathWorks) with custom software by detecting the movement of red blood cells as black lines devoid of Texas Reddextran (53). Platelet aggregation in vivo was imaged with Texas Red-dextran and Calcein AM (100 μL of 5 mM; Invitrogen) administered through a femoral vein before the imaging (54,55). Collagen (10-50 μL of 1 mg/mL dissolved in saline; Gibco) was administered through a catheter inserted into the external carotid artery to induce platelet aggregation.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported that when endothelial cells are exposed to cytoactive molecules such as histamine or calcium ionophore A23187, the secreted VWF may remain anchored to endothelial surface, providing a substrate to support platelet adhesion under flowing conditions (26)(27)(28). ADAMTS13 causes detachment of the platelets, presumably by cleaving the anchored VWF.…”
Section: Adamts13 Deficiency and Platelet Thrombosismentioning
confidence: 99%